2014
DOI: 10.1111/trf.12584
|View full text |Cite
|
Sign up to set email alerts
|

Increasing susceptibility of nitric oxide–mediated inhibitory platelet signaling during storage of apheresis‐derived platelet concentrates

Abstract: Stored PLTs showed an impairment of intracellular cGMP regulation, resulting in exceeding inhibition of agonist-induced aggregation and fibrinogen binding in the course of storage. The observed effects could be an important mechanism contributing to the storage lesion with reduced activating potential of PLTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…NO has been found to have a role in the regulation of the vascular system. For instance, it may inhibit platelet aggregation, leukocyte chemotaxis, as well as endothelial cell apoptosis (20,21). In addition, NO has been revealed to suppress VSMC proliferation in vitro (22).…”
Section: Discussionmentioning
confidence: 99%
“…NO has been found to have a role in the regulation of the vascular system. For instance, it may inhibit platelet aggregation, leukocyte chemotaxis, as well as endothelial cell apoptosis (20,21). In addition, NO has been revealed to suppress VSMC proliferation in vitro (22).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies found that storage-induced decreases in thrombin sensitivity were linked to reduced high affinity thrombin binding sites [32]. [35]. Furthermore, basal cGMP concentration and VASP-phosphorylation rises by four to five times and 1.5 times respectively over 5 days of in vitro storage [36].…”
Section: Platelet Surface Receptor Modificationsmentioning
confidence: 99%
“…16 In addition, the surface proteins expressed on stored PLTs change over time, affecting their thrombin sensitivity, and they become more sensitized to nitric oxide, which impairs their ability to aggregate. [17][18][19] Counter to the reduced aggregation with increased storage time, the accumulation of PLT microparticles amplifies thrombin formation. 20 All of these changes may impact the clinical outcomes of patients receiving PLT transfusions of differing storage age.…”
Section: Discussionmentioning
confidence: 99%